2012
DOI: 10.5897/ijbc11.231
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among commercial coffee varieties, advanced selections and museum collections in Kenya using molecular markers

Abstract: Molecular markers have effectively been applied to study genetic diversity and as markers of particular traits. This study assessed the diversity of twenty four (24) coffee genotypes using 10 Random Amplified Polymorphic DNA (RAPD) primers and 2 microsatellites (M24 and Sat 235). A total of 35 polymorphic bands were generated by the RAPD primers. The bands were scored for presence (1) and absence (0) of amplified products. The data was subjected to cluster analysis using R statistical software and a dendrogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 33 publications
0
14
0
2
Order By: Relevance
“…Most production in the country comes mainly from several Arabica varieties, such as Ruiru 11, SL28, SL34, and K7 (Kathurima et al 2012). Ruiru 11 was developed from complex crosses, involving combination of eight varieties (Van der Vossen 1985), while most varieties have been developed from single tree selection procedures (Agwanda et al 1997).…”
Section: Communicated By D Grattapagliamentioning
confidence: 99%
“…Most production in the country comes mainly from several Arabica varieties, such as Ruiru 11, SL28, SL34, and K7 (Kathurima et al 2012). Ruiru 11 was developed from complex crosses, involving combination of eight varieties (Van der Vossen 1985), while most varieties have been developed from single tree selection procedures (Agwanda et al 1997).…”
Section: Communicated By D Grattapagliamentioning
confidence: 99%
“…Coffee belongs to the genus Coffea sub-genus Coffea, family Rubiaceae and is mostly present in tropical and subtropical regions of the world [1]. The species which are economically important and cultivated world-wide are Coffea arabica (Arabica coffee) and Coffea canephora (Robusta coffee) [2]. Ethiopia is the primary center of origin and diversification for Arabica coffee [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some studies have shown variation related to nutrient-use efficiency among conilon genotypes (Favarin et al, 2007;Tomaz et al, 2009;Ferreira et al, 2013) and different nutritional requirements according to fruit ripeness stage and time of the year (Marré et al, 2015). In this context, the use of tools that can identify genetic diversity, such as hierarchical genetic clustering methods (multivariate methods), can aid in the identification of C. canephora genotypes with different genetic distances (Kathurima et al, 2012;Souza et al, 2013;Dalcomo et al, 2015;Martins et al, 2015). Among the multivariate methods, the Ward method provides an excellent strategy for quantifying genetic diversity.…”
Section: Introductionmentioning
confidence: 99%